Preparation and cell activities of lactosylated curdlan-triornithine nanoparticles for enhanced DNA/siRNA delivery in hepatoma cells. (1st December 2019) - Wang, Xia; Qi, Yuxuan; Liu, Lixia; Ganbold, Tsogzolmaa; Baigude, Huricha; Han, Jingfen
Highlights: Triornithine grafted novel curdlan gene vector was fabricated by click chemistry. Lactobionic acid ligands target deliver to liver cancer cells. Curdlan-based carriers show lower cytotoxicity and higher binding capacity than PEI. Final complex CTOL20% efficiently delivered siRNA into HepG2 cells. Abstract: A long-anticipated cancer therapy would deliver the right type of therapeutic agents to the target in control with minimal systemic toxicity. The purpose of this study was to prepare lactosylated curdlan-triornithine nanocarriers (CTOLs), and target deliver gene to hepatoma cells. Structures and biophysical properties had been elucidated with physical and chemical methods. The results revealed that those functionalized polymers can completely condense the gene into spherical nanoparticles. Cytotoxicity assay, GFP-pDNA and siRNA transfection in vitro were implemented successively. Observations showed that CTOL 20% with the highest lactose acid substitution degree targeted delivered gene into HepG2 cells over expressing ASGPR receptors and had pretty gene knockdown efficiency over 70%. Meanwhile, the carriers showed excellent biocompatibility. Our studies demonstrated that CTOLs with lower toxicity and higher gene binding capacity may serve as a potential valuable platform that can be tailored to target the liver cancer cells for therapeutic gene.